Effect of bypass fat supplementation on performance of Growing crossbred calves - Meshram, BN; Gadegaonkar, GM; Sirsat, SD (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to evaluate the effect of bypass fat supplementation on weight gain, feed intake and efficiency of feed utilization growing crossbred calves. Eighteen growing crossbred calves 6-7 months of age and 134 kg average body weight were randomly divided into three equal groups viz, Group-T0 (control), T1 and T2 on the basis of age, weight and sex with three male and three female in each group. All the groups received standard concentrate mixture for 13 weeks. The animals in treatment T1 and T2 fed on concentrate mixture supplemented with bypass fat @ 30 and 60 g per calf per day, respectively. The average body weight gain, DM intake, TDN and DCP intake by calves from group T2 was significantly (P<0.01) higher than group T0 and T1. The efficiency of feed utilization in terms of DM, TDN and DCP intake per kg gain was non significant. The nutrient digestibility was higher for treatment groups supplemented with bypass fat. Thus it was concluded that supplementation of bypass fat @60 g per calf per day was beneficial for improving the overall growth performance of calves.